Study of optimization conditions for inorganic/organic film development coating on aluminum alloy A5083 for improving the corrosion resistance - Naknikham, Usuma; Youngthin, Itsari; Tapasa, Kanit (Bulletin of Applied Sciences, 2022)
Aluminium alloy A5083 is commonly in for offshore industries since it has higher corrosion resistance by creating an oxide film protecting surfaces. However, the protective film can be destroyed under corrosive conditions like marine environment containing chloride and fluoride ions with alkalinity. To prevent the corrosion, an inorganic/organic film is applied by coating on aluminium alloy surfaces. The objective of this study was to investigate the effects of different organic precursors on corrosion resistance of the aluminium alloy under basic condition. The amounts of organic precursors and water contents in the hybrid inorganic/organic thin films coating were also studied. The hybrid films were prepared by sol-gel method containing an inorganic precursor, TEOS (Tetraethyl orthosilicate), and different organic precursors, namely AEAPS (3-(2-Aminoethyl aminopropyl trimethoxysilane), AMEO (3-Aminopropyl triethoxysilane), GPTMS (3-Glycidoxypropyl trimethoxysilane), MTMS (Methyl trimethoxysilane) and OTES (Octyltriethoxysilane). The ratios between inorganic and organic precursor were varied from 100:0, 90:10, 80:20, 70:30 and 60:40 by volume. In addition, the molar ratios of TEOS to water at different ratios, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7 and 1:8 were applied. The thin film named 806TOT consisted with TEOS:OTES ratio at 80:20 and TEOS to water ratio at 1:6 showed the highest hydrophobic property with 103.09±0.35º of contact angle. The potentiodynamic technique was employed to test corrosion resistance using 3.5 wt% NaCl. The results exhibited that 806TOT had the lowest rate of corrosion with 0.78 x 10-3 mm per year equivalent. This number is higher 50 times over aluminium alloy without coating.